Emerging Threats on Video-on-Demand Platforms: A Content Analysis of Alcohol, Tobacco, and Drug Imagery in Turkish Films and Series - Maden, Okan; Kurum, Süheyla; Yurdakul, Şefik; Ünal, Egemen; Gökler, Mehmet Enes (Addicta: The Turkish Journal on Addictions, 2025)
Digital platforms, through video-on-demand services, reach large audiences, with Turkish content gaining international popularity. Exposure to imagery of alcohol, tobacco, and drugs may pose an addiction risk. This study examined the frequency of these images in Turkish films and series. The popular tenfilms and ten series in Turkish, according to internet movie database, were analyzed. The content was divided into 5-minute intervals, and 304 intervals were evaluated for alcohol, tobacco, and drug imagery. Mann–Whitney U test and Kruskal-Wallis tests were used for analysis. 64.47% of the 304 intervalscontained at least one image of alcohol, tobacco, or drugs: Alcohol appeared in 50.33%, tobacco in 28.95%, and drug imagery in 0.99%. No differences were found across platforms, genres, or between films and series. This study was the first to analyze alcohol, tobacco, and drug imagery in Turkish content on digital platforms. Stricter regulation is recommended due to their potential contribution to addiction.